2015
DOI: 10.1530/erc-15-0402
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-deprivation increases thyroid cancer cells sensitivity to metformin

Abstract: Metformin inhibits thyroid cancer cell growth. We sought to determine if variable glucose concentrations in medium alter the anti-cancer efficacy of metformin. Thyroid cancer cells (FTC133 and BCPAP) were cultured in high-glucose (20 mM) and low-glucose (5 mM) medium before treatment with metformin. Cell viability and apoptosis assays were performed. Expression of glycolytic genes was examined by real-time PCR, western blot, and immunostaining. Metformin inhibited cellular proliferation in high-glucose medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 37 publications
3
40
0
Order By: Relevance
“…Metformin has been reported to inhibit the cell growth and reverse the drug-resistance in some cancers by reducing the production of ATP [ 38 , 39 ]. In addition, although metformin has been reported to increase chemosensitivity and target PKM2 in routine cancer cells [ 40 , 41 ], effect of metformin on cancer models with acquired drug resistance is unclear. In the present study, we demonstrated that metformin treatment decreased the expression of PKM2 in carboplatin-resistant NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin has been reported to inhibit the cell growth and reverse the drug-resistance in some cancers by reducing the production of ATP [ 38 , 39 ]. In addition, although metformin has been reported to increase chemosensitivity and target PKM2 in routine cancer cells [ 40 , 41 ], effect of metformin on cancer models with acquired drug resistance is unclear. In the present study, we demonstrated that metformin treatment decreased the expression of PKM2 in carboplatin-resistant NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid cancer, as the most common endocrine malignancy, has a rapidly increasing incidence in world-wide recently 12 . PTC, as the most common type of thyroid cancer, accounts for 70-90 % of all thyroid malignancies 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed a differential susceptibility of different thyroid cancer cell lines to the antiproliferative effects of metformin, and showed that the availability of metabolic substrates (i.e. glucose) modifies the response to metformin in vitro (15). This observation formed the rationale to test the role of mGPDH in growth and metabolism of thyroid cancer cell lines in vitro , metastatic mouse models in vivo and in a transgenic mouse model that spontaneously develops thyroid cancer.…”
Section: Introductionmentioning
confidence: 96%